P53 expression in hepatocellular carcinoma in a population in Singapore with endemic hepatitis B virus infection. Issue 3 (March 1995) - Wee, A; Teh, M; Raju, G C
Abstract : AIMS--To study the expression and clinical significance (if any) of p53 protein in hepatocellular carcinomas (HCC) arising in a population with endemic hepatitis B virus (HBV) infection. METHODS--Immunohistochemical staining was performed on formalin fixed, paraffin was embedded histological sections of 46 HCC cases using an antihuman p53 monoclonal antibody; serial sections were also stained for hepatitis B surface antigen (HBsAg), hepatitis B core antigen (HBcAg) and alpha fetoprotein (AFP). Nuclear p53 staining was assessed according to intensity (absent, weak or strong) and extent (< 5%, 6-25%, 26-50%, and > 50%) of positive cells. Tissue HBsAg, HBcAg and AFP were recorded as absent or present. RESULTS--The p53 protein was expressed in 35% (16 of 46) of HCCs; the positive rate in grade III/IV tumours (13 of 31; 42%) was higher than in grade I/II tumours (three of 15; 20%) but this was not statistically significant. HBsAg positive tumours showed almost the same proportion of p53 staining (11 of 29; 38%) as HBsAg negative ones (five of 17; 29%). CONCLUSIONS--The p53 protein was expressed in 35% of HCC cases. There was no statistically significant correlation between HBV infection and p53 protein expression. Similarly, there was no definite correlation between p53 positivity and tumour size, histological grade or vascular invasion.